2017
DOI: 10.1007/jhep09(2017)061
|View full text |Cite
|
Sign up to set email alerts
|

On the importance of electroweak corrections for B anomalies

Abstract: Abstract:The growing experimental indication of Lepton Flavour Universality Violation (LFUV) both in charged-and neutral-current semileptonic B-decays, has triggered many theoretical interpretations of such non-standard phenomena. Focusing on popular scenarios where the explanation of these anomalies requires New Physics at the TeV scale, we emphasise the importance of including electroweak corrections to obtain trustable predictions for the models in question. We find that the most important quantum effects a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
180
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 139 publications
(185 citation statements)
references
References 128 publications
4
180
0
Order By: Relevance
“…Thus we have clear target observables that we can affect with a small number of LQ Yukawa couplings. In the context of SM complemented with effective operators (SM-EFT) it has been shown that NP models contributing to dimension-6 operators made out of left-handed quark and lepton doublets can explain both neutral-and charged-current LFU anomalies [17,32,50,53,54]. However, in an explicit NP model these effective interactions could be JHEP10(2017)188 correlated, unlike in the effective theory, 2 with other observables.…”
Section: Model Setupmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus we have clear target observables that we can affect with a small number of LQ Yukawa couplings. In the context of SM complemented with effective operators (SM-EFT) it has been shown that NP models contributing to dimension-6 operators made out of left-handed quark and lepton doublets can explain both neutral-and charged-current LFU anomalies [17,32,50,53,54]. However, in an explicit NP model these effective interactions could be JHEP10(2017)188 correlated, unlike in the effective theory, 2 with other observables.…”
Section: Model Setupmentioning
confidence: 99%
“…As it has been pointed out recently in the literature [54,55,62] the LFU observable R τ / τ , defined as a ratio B(τ → νν)/B(µ → eνν), and normalized to the SM prediction of this…”
Section: Leptonic Decays: W → τν τ → ννmentioning
confidence: 99%
“…It should be noticed that strong constraints on this setup arise when considering radiative electroweak corrections as discussed in refs. [212,213].…”
Section: Jhep07(2017)089mentioning
confidence: 99%
“…The latter has been recently shown in refs. [212,213] to lead to a rich phenomenology, especially in EWPO and τ sector.…”
Section: B Semi-leptonic Decaysmentioning
confidence: 99%
“…Since the implied scale of new physics is rather low [34], the main challenge is to reconcile it with the non-observation of related signals in (other) flavour changing processes (e.g. [35]), electroweak precision observables, τ decays [36,37], and high-p T searches [15,38].…”
Section: Combined Explanation With R(d ( * ) ) Anomaly (Hints In CC Bmentioning
confidence: 99%